I - You - Work as a source of knowledge. From neo-Kantianism to hermeneutics: Cassirer and Ricoeur - Węgrzyn, Marta (Hybris, 2020)
An attempt to compare the epistemological positions of two thinkers coming from different philosophical traditions requires turning to the sources of both philosophical programs. This will allow us to reveal the common and differentiating features of the described projects. On the one hand, we have Cassirer, the heir to neo-Kantianism and the creator of symbolism, on the other, we are rooted in the tradition of reflective philosophy and phenomenological hermeneutics, Ricoeur. Despite many differences in epistemological assumptions, we can find similar positions in both philosophers.The concurrence of the three Cassirerow base phenomena with three hermeneutic horizons manifests itself - as we will try to demonstrate - in the concept of the Work. The hermeneutic intuition of Cassirer turns into Ricoeur's reflection on self-understanding in the face of a work that affects our perception of the world and thinking about ourselves.In the article, we will consider how the contemporary philosophy of culture developed by Cassirer is taken up by contemporary hermeneutics. Is the convergence of the three base phenomena with the three horizons that combine with each other in the process of interpretation in the juxtaposition of the philosophy of culture with contemporary hermeneutics? Do we have the right to compare Cassirerow's base phenomena, I - You -Work is with hermeneutic communication which is presented on the line Author (Creator) -Text (Work) - Reader (Receiver)?